The profile of subjects with suspected coronary artery disease who have atypical chest pain symptoms - Premsagar, P.; Naidoo, D.P. (SA Heart Journal, 2025)
Background: This study describes the risk factor profile of subjects with coronary artery disease (CAD) who present with atypical chest pain. Method: Hospital records of patients with chest pain who did not satisfy the criteria for typical angina and who underwent both sestamibi nuclear imaging and coronary angiography were evaluated over a 6 year period (2002 - 2008). Results: Amongst 5 378 subjects referred for evaluation of myocardial ischaemia to a tertiary hospital, the prevalence of atypical / non-anginal pain was 9.9% (531 patients). Of the 173 subjects who underwent both nuclear scans and coronary angiography, 99 (M 66, F 33) (57%) had epicardial CAD at angiography (>50% stenosis) with equal distribution of single, double and triple vessel disease. There was no difference in the pretest probability of CAD in subjects with and without CAD (20.5% vs. 21.9% p=0.891). Neither the number of chest pain criteria nor the individual pain characteristics were associated with the presence of CAD (p>0.05). CAD was more likely in the middle age and older subjects (p<0.001), in males (p<0.001) and in those who smoked (LR 5:2 p=0.001). On multivariate analysis age, smoking, waist circumference and gender emerged as predictors of CAD. Clustering of 3 or more risk factors was associated with the presence of myocardial perfusion deficits (p=0.001). Conclusion: Characterisation of chest pain symptomatology did not prove to be helpful in the detection of CAD among subjects with a low pretest probability. Decision-making and triage should be supported by a positive smoking history and risk factor clustering.